Recent developments in the modeling of (n,γ) reactions with FIFRELIN - Chalil, Achment; Materna, Thomas; Litaize, Olivier; Chebboubi, Abdelaziz (HNPS Advances in Nuclear Physics, 2022)
Nowadays, the accuracy of experimental results relies more and more on detailed simulations. In the STEREO experiment, the interaction of neutrinos in the liquid scintillator is signed by a n-capture on a Gd atom. The FIFRELIN predictions of the Gd γ-cascades were shown to significantly improve the Data/MC agreement. In the CRAB method, lately proposed to calibrate cryogenic particle detectors at low energy (100 eV), the FIFRELIN cascades of the W and Ge isotopes played a central role in the feasibility study of the method. The FIFRELIN code employs a Monte Carlo Hauser-Feshbach framework based on Bečvár’s algorithm. A sample of nuclear level schemes is generated for a specific isotope of interest, taking into account the uncertainties from nuclear structure. In this work, new improvements on the FIRELIN de-excitation process are reported. Angular correlations of γ-rays in the de-excitation process have been implemented in order to provide a more accurate description of the γ-ray cascades. The anisotropy of the γ-rays with respect to the axis of a previously emitted γ-ray is modeled using the angular correlation formalism, which requires input of the spins and multipolarities of the states involved in the FIFRELIN cascade. Furthermore, the simulation of primary γ-rays emitted from (n,γ) reactions has been updated using the EGAF database.